Campanha nova era Piticas - Benavides, Andre (2021)
The name Piticas came from a family nickname, giving name to the dream of two brothers Vinicius and Felipe, who after living in the United States for ten years, returned to Brazil to undertake, give life to one of the largest franchises in the geek sector in the country and be the biggest pop culture brand in Latin America. The brothers founded their first kiosk in 2010 and since then they have not stopped growing, expanding their franchises across the country. Today, the factory produces up to 30,000 shirts a day and sells more than 300,000 pieces monthly, further proving its strength in the market. With the growth of franchises, new challenges have arrived. The standardization of all stores and kiosks, the planning and carrying out of actions with each franchisee and the alignment of logistics, such as the delivery of products throughout Brazil through e-commerce, started to be more difficult to be carried out. Piticas has already been planning new projects, a new visual identity, a closer relationship with the public, a different and innovative shopping experience, changing its positioning in the market and further expanding its communication channels, as you will see later. Thinking about how to face and bring innovative and assertive solutions, we at the Drop agency drew up a strategic plan, reaching all the pain presented with achievable and authentic solutions. We will have an action to announce the new visual identity of the brand, reinforcing the repositioning in the market and announcing the changes that will accompany this new phase. With the arrival of new projects in digital media, we will carry out actions on social networks, expanding our reach and reaching new audiences, actions in out of home (OOH) format, media such as radio and television, digital media, advertisements, gifts, lives, events , exhibition, shopping experience marketing and Comic Con Experience. We will also carry out an internal action aimed at franchisees, using a program to improve the general standardization of all franchises and benefit each storekeeper individually, working to encourage each entrepreneur who believes in the brand and aims for growth throughout the network. When preparing this plan, we chose to show the strength of the brand internally and externally, valuing the already established identity, presenting a new positioning in a fun way, achieving its goals always focusing on growth and its consolidation. Strengthening the growth of each franchisee and the expansion in the national territory, showing that Piticas offers the best in the geek universe.